2013
DOI: 10.1016/j.placenta.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Detection of KATP channels subunits in human term placental explants and evaluation of their implication in human placental lactogen (hPL) and human chorionic gonadotropin (hCG) release

Abstract: The present findings suggest that the human term syncytiotrophoblast might be endowed with KATP channels. Further studies should clarify their implication in the syncytiotrophoblast ionic homeostasis and hormone regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…According to the specificity and the concentration of 4-AP and TEA used, the targeted K + channels belong mainly to the K V channel family [ 23 ]. Indeed, K + channels belonging to other families such as ATP-sensitive K + channels are not involved in hCG secretion [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the specificity and the concentration of 4-AP and TEA used, the targeted K + channels belong mainly to the K V channel family [ 23 ]. Indeed, K + channels belonging to other families such as ATP-sensitive K + channels are not involved in hCG secretion [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, it has been shown that ABCC1 and ABCC9 are expressed in the amniotic and chorionic membrane [22,23]. However, to our knowledge, expression of SLCO4C1 and SLCO5A1 in placental tissues has not been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, they are cultured in 2–8% oxygen, which is most suitable for villi growth [ 80 ]. Studies have demonstrated that placental explants can produce large amounts of hormones, such as hCG and hPL, within a few hours of culture [ 81 ].…”
Section: Placental Explantsmentioning
confidence: 99%